The formation of stress management module via liver conscious concept in handling work stress among teachers - Mohd Shahril, Othman
A module (Modul Pengurusan Tekanan-MPT) was developed with liver consciousness concept in managing work stress among teachers in Malaysia. The module consists of five main units to foster teachers' stress problems. These units namely; are (1) identification, (2) current scenario, (3) scenarios to be achieved, (4) strategies and actions (5) prevention strategies. In the introduction part, it deals with the ice-breaking and explains the content of the module, and then activities will be carried out in the current scenario to acquire the skills to know, while in the third part is the scenario to be achieved, aimed to train the skill of fact understanding. The next section is the strategy of action, where the participants will be equipped with unconditionally acceptance and avoiding negative emotional skills. Finally, the last part is the prevention strategies which involved with rationalizing and problem solving skills. An intervention by using the module will be carried out on those teachers with high levels of stress in testing the effectiveness of it. Then, the same group will be retested with a set of stress questionnaire. The finding pointed outs the effectiveness of the module that is either reducing stress to low or middle levels. Subsequently, the module will be tested its effectiveness among another group of respondents. If the results obtained are remained the same, it is expected that the module manages in reducing stress effectively.